The Degree of School Principals' Contribution to Achieving the Goals of Tourism Education at the Schools in the Education Directorate of the Northern Jordan Valley from the Point of View of Teachers of Social Studies - Mohammad Albataineh; Mohammad Alfursan; Muneera Alshurman (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to reveal the degree of contribution of school principals to achieving the objectives of tourism education in light of the variables of gender, academic qualification and years of experience. Its sample consisted of (71) teachers of social studies from the schools of the Northern Jordan Valley. The study used a descriptive survey method. To achieve the objectives of the study, a questionnaire consisting of (29) items was built. The study concluded that the degree of managers' contribution to achieving the goals of tourism education came to a (high) degree. Its results also indicated that there were no statistically significant differences between the average responses of the sample members due to the variables (sex, educational qualification and years of experience). The study recommended the necessity of enhancing the role of school principals in achieving the objectives of tourism education through training courses and educational meetings.